Guinea : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Guinea's economic performance over the past four years fell significantly short of the authorities' ambitious projections. Economic growth averaged 1.8 percent during 2012-15, significantly below the performance of peers, and GDP per capita is estimated to have fallen, likely inducing an increase in poverty. The economy is recovering from the effects of the Ebola epidemic. Growth is projected to rebound to 3.7 percent in 2016, on the back of higher electricity provision from the Kaleta hydroelectric dam and a strong increase in bauxite production. The medium-term outlook is favorable, but continues to be clouded by downside risks.